Odpowiedź :
(4x+4)²-5²=0
(4x-4-5)(4x-4+5)=0
(4x-9)(4x+1)=0
4x-9=0 v 4x+1=0
4x=9/:4 v 4x=1/:4
x=9/4 v x=1/4
9²-(3x+7)²=0
(3x-7-9)(3x-7+9)=0
(3x-16)(3x+2)=0
3x=16/:3 v 3x=2/:3
x=16/5=5⅓ v x=⅔
2x-(x+2)²=0
(2x-x-2)(-2x-x-2)=0
x=2 v -3x=2/:(-3)
x=2 v x=-1½
(4x-4-5)(4x-4+5)=0
(4x-9)(4x+1)=0
4x-9=0 v 4x+1=0
4x=9/:4 v 4x=1/:4
x=9/4 v x=1/4
9²-(3x+7)²=0
(3x-7-9)(3x-7+9)=0
(3x-16)(3x+2)=0
3x=16/:3 v 3x=2/:3
x=16/5=5⅓ v x=⅔
2x-(x+2)²=0
(2x-x-2)(-2x-x-2)=0
x=2 v -3x=2/:(-3)
x=2 v x=-1½
4(x+1)²-25=0
(4x+4)²-5²=0
(4x-4-5)(4x-4+5)=0
(4x-9)(4x+1)=0
4x-9=0 v 4x+1=0
4x=9/:4 v 4x=1/:4
x=9/4 v x=1/4
81-(3x+7)²=0
9²-(3x+7)²=0
(3x-7-9)(3x-7+9)=0
(3x-16)(3x+2)=0
3x=16/:3 v 3x=2/:3
x=16/5=5⅓ v x=⅔
4x² - (x+2)²=0
(2x)²-(x+2)²=0
(2x-x-2)(-2x-x-2)=0
x=2 v -3x=2/:(-3)
x=2 v x=-1½
(4x+4)²-5²=0
(4x-4-5)(4x-4+5)=0
(4x-9)(4x+1)=0
4x-9=0 v 4x+1=0
4x=9/:4 v 4x=1/:4
x=9/4 v x=1/4
81-(3x+7)²=0
9²-(3x+7)²=0
(3x-7-9)(3x-7+9)=0
(3x-16)(3x+2)=0
3x=16/:3 v 3x=2/:3
x=16/5=5⅓ v x=⅔
4x² - (x+2)²=0
(2x)²-(x+2)²=0
(2x-x-2)(-2x-x-2)=0
x=2 v -3x=2/:(-3)
x=2 v x=-1½